Pengabdian Masyarakat Dalam Rangka Pengembangan Kebun Raya Gianyar Sebagai Destinasi Wisata Usadha Di Bali - Desak Putu Citra Udiyani; Pande Ayu Naya Kasih; I Gede Suranaya Pandit (Empowerment: Jurnal Pengabdian Masyarakat, 2023)
Usadha or herbal-based traditional medicine has been widely used by the people of Indonesia, especially Bali. Bali is considered to have a great potential to become an area for developing herbal tourism destinations. Gianyar Botanical Garden is one of the tourist destinations in Bali which is suitable to be developed into a usadha tourist destination. This community service activity aims to provide initial ideas for the development of the Gianyar Botanical Gardens as an usadha tourist destination through focus group discussions, socialization, counseling, and provision of additional plant collections Tulsi "the queen of herbs", and promotional assistance through social media. The entire series of activities had been carried out in July 2022. The activities were also combined with the field visit activities of the Elective Study of Balinese Herbal Medicine, Faculty of Medicine and Health Sciences, Warmadewa University. It is expected that the program will not only be able to increase the branding of the Gianyar Botanical Gardens but also herbal based medicine, especially among millennials.